Romania’s Main Role in the Current Global Economic Context - GURGU, Elena; ZORZOLIU, Raluca (Annals of Spiru Haret University. Economic Series, 2016)
The purpose of this article is to highlight Romania’s role in the current international economic context. The analysis herein refers to the domestic macroeconomic developments of our country in 2015, which will influence in the future the evolution of the Romanian economy. In this article we will cover Romania’s current international position, Romania’s external position, the developments in the labour market from Romania, as well as the international context in which our country finds itself also.